Analysis of Maximum Aerobic Capacity (VO2max) of Tulungagung Handball Male Athletes - Wicahyo, Tegar; Kurniawan, Rubbi; Pradipta, Anangga Widya (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2024)
Maximal aerobic capacity (VO2max) is a key indicator of cardiovascular fitness and an athlete's ability to maintain physical performance in intense sports activities, especially handball. Tulungagung, as one of the regions in East Java that is actively developing handball sports, has excellent potential to produce outstanding athletes. This study aims to describe the VO2max of male handball athletes from Tulungagung. The research subjects were active male handball athletes from Tulungagung, selected through purposive sampling based on the following criteria: aged 18-21 years, with a minimum of two years of competitive experience, and regularly participating in training with a group of 15 people. The research instrument used is the Multistage Fitness Test (MFT), also known as the beep test, to measure VO2max. The results showed that male handball athletes in Tulungagung had an average VO2max of 47.693 ml/kg/min, with the majority, as much as 67% being in the Excellent and Superior categories.